The longitudinal relationships of neophobia with family life satisfaction: a cross-lagged panel analysis of happiness externality and family harmony - Korun, Ali Berke; Satici, Seydi Ahmet (SPRINGER, 2026)
This study investigated the longitudinal associations between neophobia, externality of happiness, family harmony, and family life satisfaction. Data were collected from 315 Turkish adults (M = 24.14 years) across two waves with a five-month interval. Applying a Cross-Lagged Panel Model (CLPM) to assess temporal precedence, the results revealed that neophobia at Time 1 significantly and positively predicted family harmony at Time 2. This longitudinal link, while counterintuitive, suggests that a dispositional resistance to novelty may function as a stabilizing factor within the family system by potentially reinforcing established routines. Furthermore, neophobia was found to positively predict the externality of happiness, which in turn had a negative impact on family harmony. Finally, family harmony emerged as a significant predictor of family life satisfaction. The findings are discussed within the frameworks of Family Systems Theory and Self-Determination Theory, emphasizing the role of individual dispositions in maintaining relational stability in specific cultural contexts.
Keywords: Neophobia; Family harmony; Externality of happiness; Family life satisfaction; HEALTH; Psychology